Long-Term Consequences of Repeated School Closures During the COVID-19 Pandemic for Reading and Mathematics Competencies - Schult, Johannes; Mahler, Nicole; Fauth, Benjamin; Lindner, Marlit Annalena (Frontiers in Education, 2022)
School closures during the first wave of the COVID-19 pandemic in early 2020 were associated with attenuated learning gains compared to pre-pandemic years. In Germany, two further pandemic waves led to school closures and periods of remote learning between December 2020 and May 2021. The present study investigates the academic achievement of all incoming fifth-graders in the federal state of Baden-Württemberg before and during the pandemic, using educational large-scale assessment results in reading and mathematics. Each year, the assessments took place at the beginning of the school year in September (each n > 84,000). The comparison of average competence levels in 2021 with pre-pandemic years (2017–2019) indicates that the downward trend that was observed after the first pandemic wave in 2020 came to a halt in the domain of reading and continued at a slower rate in the domain of mathematical operations. Achievements in the mathematical domain of numbers even rebounded to pre-pandemic levels. Longer periods of school closures were associated with larger learning losses. Additional analyses showed larger learning losses for the group of low-achieving students and for schools with less socio-cultural capital. The partial rebound of learning outcomes suggests that most teachers and students successfully adapted to the pandemic situation in 2021. Still, disadvantaged student groups are at high risk of further substantial learning losses due to school closures that may negatively affect their future education. Accordingly, disadvantaged student groups in particular should receive additional support to compensate for the loss of learning opportunities in the classroom.